2018
DOI: 10.14419/ijet.v7i2.7.10296
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent vehicle black box using IoT

Abstract: Millions of people die due to the accidents. The main purpose of this paper is to provide vehicle safety and a solution that automatically alert the driver to be cautious. In this paper we continuously monitor the vehicle performance using sensors and the behavior of driver with the use of IoT Technology. The Vehicle black box receives the information from various sensors like the breath analyzer, acceleration and the distance of surrounding vehicles along with push and panic button. When the driver alcohol co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Although several studies were found to implement IoT with an alcohol detection technology [41,45,46,51], this paper presents a concept for implementing cellular IoT with a breath analyzer equipped with input (number pad) and output (LCD display) devices to enable using the device for collecting data from multiple participants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several studies were found to implement IoT with an alcohol detection technology [41,45,46,51], this paper presents a concept for implementing cellular IoT with a breath analyzer equipped with input (number pad) and output (LCD display) devices to enable using the device for collecting data from multiple participants.…”
Section: Discussionmentioning
confidence: 99%
“…Other vehicle-related technologies have been presented as well. For instance, Anil Kumar et al [51] introduced a black box that utilizes IoT technologies to detect alcohol and danger in the surroundings and act upon prepared actions such as identifying the location and alerting government representatives and emergency contacts. Nirosha et al [52] developed a prototype of a device that senses alcohol in the atmosphere of the car and then reports to the nearest police station.…”
Section: Introductionmentioning
confidence: 99%
“…The study conducted by Anil Kumar et al [23] aims to enhance vehicle security and raise driver awareness through IoT technology. It continuously analyzes vehicle performance and driver behavior using various sensors, including a breath analyzer, accelerometers, and distance sensors between other vehicles.…”
Section: Related Workmentioning
confidence: 99%
“…discussed a technique to transfer traffic information to the vehicle [28]. Anil Kumar explains a technique to monitor driver fatigue to prevent vehicle accident [29]. Joshua Alvaro Fitzhan explains the challenges of smart contracts and how it is used in Indonesian industries [30].…”
Section: Related Workmentioning
confidence: 99%